2006
DOI: 10.1186/1743-422x-3-27
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of histone deacetylation in 293GPG packaging cell line improves the production of self-inactivating MLV-derived retroviral vectors

Abstract: Background: Self-inactivating retroviral vectors (SIN) are often associated with very low titers. Promoter elements embedded within SIN designs may suppress transcription of packageable retroviral RNA which in turn results in titer reduction. We tested whether this dominant-negative effect involves histone acetylation state. We designed an MLV-derived SIN vector using the cytomegalovirus immediate early enhancer-promoter (CMVIE) as an embedded internal promoter (SINCMV) and transfected the pantropic 293GPG pac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 49 publications
1
7
0
1
Order By: Relevance
“…For pseudoparticles used to generate cells stably expressing a protein of interest, the cells were transfected with pVSV-G encoding the G protein for the Vesicular stomatitis virus (VSV), the lentiviral packaging plasmid pCMV_ΔR8-74 and the pWPI (from Didier Trono (Addgene plasmid # 12254) encoding either the wild type or mutant (TIM-1 or Axl) and a blasticidin resistance gene. Sodium butyrate was added 24 h post transfection in order to boost plasmid transcription [ 56 ]. For cell entry experiments, the pseudoparticles were generated using a plasmid encoding for a glycoprotein of the virus of interest (CHIKV, EBOV or VSV), the lentiviral packaging plasmid pCMV_ΔR8-74, and a pWPI plasmid encoding a luciferase gene as a reporter protein.…”
Section: Methodsmentioning
confidence: 99%
“…For pseudoparticles used to generate cells stably expressing a protein of interest, the cells were transfected with pVSV-G encoding the G protein for the Vesicular stomatitis virus (VSV), the lentiviral packaging plasmid pCMV_ΔR8-74 and the pWPI (from Didier Trono (Addgene plasmid # 12254) encoding either the wild type or mutant (TIM-1 or Axl) and a blasticidin resistance gene. Sodium butyrate was added 24 h post transfection in order to boost plasmid transcription [ 56 ]. For cell entry experiments, the pseudoparticles were generated using a plasmid encoding for a glycoprotein of the virus of interest (CHIKV, EBOV or VSV), the lentiviral packaging plasmid pCMV_ΔR8-74, and a pWPI plasmid encoding a luciferase gene as a reporter protein.…”
Section: Methodsmentioning
confidence: 99%
“…This in turn improves RNA transcription and consequently vector production. 68 However, the effect of sodium butyrate remains controversial as the gain in vector productivity is not consistent from one author to another one. For instance, Ansorge et al 65 reported a titer increase of more than 10-fold using 5-mmol/l sodium butyrate for the production of VSV-g-pseudotyped LV.…”
Section: Lentiviral Vector Productionmentioning
confidence: 99%
“…We further improved the volumetric titer by adding sodium butyrate to the culture medium. Sodium butyrate is a well-known histone deacetylase inhibitor in mammalian cells; by preventing DNA compaction, it improves mRNA transcription and concomitantly, protein production 40 . Despite small increases in LV production during short production periods the presence of sodium butyrate impaired virus production in long term cultures (Fig.…”
Section: Discussionmentioning
confidence: 99%